Prevalence and Its Associated Factors of Maternal Stress among Mothers of Hospitalized Children Admitted to a Tertiary Health Care Center of Central Nepal - Dahal, Nirmala; Dhimal, Sita; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2024)
Background: Stress is a universal phenomenon and all person experiences it. Stress can result from both negative and positive experiences. Stress is a physical and emotional state always present in the person. Experience of having a child hospitalized can be profoundly stressful for mothers, impacting their mental and emotional well-being. The limited access to resources, cultural norms, and quality of healthcare services may further exacerbate maternal stress. This research aimed to find out factors associated with stress among mothers of hospitalized children at college of medical science, teaching hospital, Bharatpur, Chitwan. Method: The descriptive cross-sectional research was carried out among 131 mothers were obtained information through structured interview by face-to-face interview technique. Filled up questionnaires were checked for accuracy and completeness and coded, entered into computer system and analyzed using SPSS (version 18.0). Chi-square test was used to find out association between the variables. Result: The study result indicated that majority of respondents were age of 21 to 30 years (56.5%), followed Hinduism (82.4%), residing in urban areas (65.6%), and predominantly housewives (67.2%). Regarding education, a significant portion attained secondary level education (40.5%). The proportion of mothers expressed stress, with 80.9% experiencing moderate stress. Association between stress levels and various factors were explored, revealing significant relationships with educational status (p < 0.001) and the number of children (p = 0.019), among socio-demographic variables. Child-related factors such as receiving help for treatment costs (p = 0.001) also showed significant associations with maternal stress. Conclusion: The study result reveals that mothers of hospitalized children at college of medical science, Teaching Hospital, experienced significant stress, with socio-demographic factors, financial challenges and treatment costs.